Upaya Memperkuat Resiliensi Pendidikan Inklusi Melalui Rumah Mengaji Di Masa Pandemi - Farida Isroani; Ida Fauziatun Nisa’ (al-Afkar, Journal For Islamic Studies, 2023)
Every parent expects their child to be born into this world normally. Every child has the right to grow and develop, get an education, and other rights. The fulfillment of this right is no exception for children with disabilities or called diffable. Not all parents can accept their children as children with disabilities. and give full love. Currently there are not many parents who can accept their children with disabilities with a sincere heart, this can be seen from the different way of parenting in general, which has an impact on the lack of fulfillment of the rights and needs of children with disabilities. Such parenting problems need to be fixed. Good parenting is expected to fulfill their needs and rights to function socially, both to fulfill love, protection and education. If the fulfillment of the right to education can be obtained in Special Schools and inclusive schools with a limited duration of study time, then parenting assistance is needed through disabled learning houses. There are learning houses for the disabled. The teaching staff comes from students with the guidance of lecturers according to their fields. The activities include providing additional learning hours outside of school hours, teaching children with disabilities to recite the Koran. As is the case, for children with disabilities who are deaf and speech impaired, they are taught using sign language learning media, both alphabetically and hijaiyah. Thus, the real goal of education will be realized, namely equal and decent education for all.